Evaluation of Sterilisation Techniques for Regenerative Medicine Scaffolds Fabricated with Polyurethane Nonbiodegradable and Bioabsorbable Nanocomposite Materials. (3rd October 2018) - Griffin, Michelle; Naderi, Naghmeh; Kalaskar, Deepak M.; Malins, Edward; Becer, Remzi; Thornton, Catherine A.; Whitaker, Iain S.; Mosahebi, Ash; Butler, Peter E. M.; Seifalian, Alexander M.
Abstract : An effective sterilisation technique that maintains structure integrity, mechanical properties, and biocompatibility is essential for the translation of new biomaterials to the clinical setting. We aimed to establish an effective sterilisation technique for a biodegradable (POSS-PCL) and nonbiodegradable (POSS-PCU) nanocomposite scaffold that maintains stem cell biocompatibility. Scaffolds were sterilised using 70% ethanol, ultraviolet radiation, bleach, antibiotic/antimycotic, ethylene oxide, gamma irradiation, argon plasma, or autoclaving. Samples were immersed in tryptone soya broth and thioglycollate medium and inspected for signs of microbial growth. Scaffold surface and mechanical and molecular weight properties were investigated. AlamarBlue viability assay of adipose derived stem cells (ADSC) seeded on scaffolds was performed to investigate metabolic activity. Confocal imaging of rhodamine phalloidin and DAPI stained ADSCs was performed to evaluate morphology. Ethylene oxide, gamma irradiation, argon plasma, autoclaving, 70% ethanol, and bleach were effective in sterilising the scaffolds. Autoclaving, gamma irradiation, and ethylene oxide led to a significant change in the molecular weight distribution of POSS-PCL and gamma irradiation and ethylene oxide to that of POSS-PCU (p<0.05). UV, ethanol, gamma irradiation, and ethylene oxide caused significant changes in the mechanical properties of POSS-PCL (p<0.05). Argon was associated with significantly higher surface wettability and ADSC metabolic activity (p<0.05). In this study, argon plasma was an effective sterilisation technique for both nonbiodegradable and biodegradable nanocomposite scaffolds. Argon plasma should be further investigated as a potential sterilisation technique for medical devices.